Treatment of Bronchopneumonia with Spiramycine (Rovamycine) - Soejono Soejono; Moeljono S. Trastotenojo; Harsoyo N. (Indonesian Pediatric Society, 1976)
Fifty-seven children with bronchopneumonia, comprising 32 male and 25 female, were admitted to the Department of Child Health, Dr. Kariadi Hospital, Semarang, during the period of May 1972 - May 1973. Varying in ages between 16 days and 7 years, 36 of them were less than one year old. They were treated with spiramycine (Rovamycine) given orally in a dosage of 50 mg/kg body weight daily in three divided doses. The failure was 9 out of 57 cases (15.8%) and in infants 7 out of 36 cases (19.4%). The culture of infants revealed 36.1% staphylococcus and in older children showed 4.8%. All cases of staphylococcus as a single cause which was treated with spiramycine gave good results. No side effects of spiramycine were noted. The study showed that spiramycine has a value in the treatment of childhood bronchopneumonia especially in staphylococcal injections in infants.